Capacity planning and performance measurement for automobile service centre using simulation. (1st January 2012) - Sharma, Rishu; Garg, Suresh
After sales service plays vital role in industries to achieve customer satisfaction and retention and acts as relevant source of revenue. Automobile service centre (ASC) involves the activities related to repair and service operation after purchase of car. ASC is a complex system with features of job shop production, service management, maintenance management and supply chain management. ASC has to provide good repair and service with on time delivery and at competitive price. To achieve this, proper design and planning of capacity is of prime importance. This paper presents the impact of capacity planning on the performance of ASC and then capacity planning schedule of ASC is done to meet the existing demand. The measures for meeting the changing demand are also suggested. Performance measurement under varying demand is studied. Since real life systems are very complex, simulation is used as the tool to study the dynamics between capacity and performance.